JURIDICAL REVIEW OF THE MARRIAGE BAN OF INDIGENOUS PEOPLES OF MIRAH VILLAGE AND GOLAN VILLAGE, SUKOREJO DISTRICT, PONOROGO REGENCY IS REVIEWED FROM LAW NUMBER 1 OF 1974 CONCERNING MARRIAGE - Amanda Salsabila Surya; Rahmatiar, Yuniar; Asyhadi, Farhan (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2024)
The existence of customary law is a source of law in Indonesia, to be precise in Mirah Village and Golan Village, Sukerojo District, Ponorogo District. There is a customary rule that prohibits the two villages from carrying out a marriage. the worst is death. This can be seen from the discrepancy that exists between the customary law of the Mirah people and the Golanese people and the national law, whereas in the national law there is nothing that regulates the prohibition of inter-regional marriages. This research contains identification of the problem of how in the villages of Mirah and Golan there was a prohibition on inter-regional marriages and how to analyze the juridical prohibition on marriages of the Mirah and Golan Indigenous Peoples when viewed from Law Number 1 of 1974 concerning Marriage. This research aims to determine the prohibition on marriage between Mirah village and Golan village and to find out the juridical analysis of the prohibition on marriage between Mirah village and Golan village when viewed from Law Number 1 of 1974 concerning Marriage. This research method uses the Normative Juridical research type. Research Results The prohibition on marriage between Mirah and Golan villages occurs because there is an oath from the ancestors which is still adhered to today and has become a legal rule for both communities and that in Law Number 1 of 1974 Article 6 and Article 8 letter F includes the rules related to the ban on marriage that occurred in the villages of Mirah and Golan.